Prevelance of Metabolic Syndromes in Faisalabad - Abbas, Muhammad; Ayub, Nida; Ilyas, Sana; Noor, Ayesha (Indus Journal of Bioscience Research, 2025)
Background: Metabolic syndrome is an increasing public health problem characterized by a group of metabolic abnormalities including insulin resistance, dyslipidemia, hypertension, central obesity, and fatty liver. These pathologies, when present at the same time, significantly increase the risk of cardiovascular diseases and type-2 diabetes. Despite its clinical importance, literature and data on the prevalence of metabolic syndrome in urban Pakistani populations remain limited. Objective: This study aimed to determine the prevalence and associated risk factors of metabolic syndrome among adults in Faisalabad, Pakistan. Methods: An observational cross-sectional study was conducted over a three-month period in Allied hospital of Faisalabad. A purposive sampling technique was used to recruit 380 participants and collect data aged 25 to 65 years. Inclusion criteria included individuals with a body mass index (BMI) >25 kg/m², a diagnosis of hypertension, diabetes, dyslipidemia, or a history of cardiovascular disease. Data were collected using structured questionnaires and validated clinical tools measuring anthropometric indices, fasting glucose, lipid profiles, and blood pressure. The prevalence of MetS was defined based on established diagnostic criteria. Results: The study showed a high prevalence of metabolic syndrome in the population. Among the main components, hypertriglyceridemia (72%), low HDL cholesterol (65%), elevated blood pressure (60%), and central obesity (58%) were the most frequently observed diseases. Additionally, insulin resistance, fatty liver, and polycystic ovary syndrome (PCOS) were commonly found among female participants. These findings were consistent with national trends and highlighted age, BMI, sedentary lifestyle, and poor dietary habits as major contributors. Conclusion: The findings emphasize a significant burden of metabolic syndrome and its components in Faisalabad. Public health interventions focusing on lifestyle modification, early screening, and community-level awareness are urgently needed to control the rising trend and prevent related cardiovascular and metabolic complications.